Evaluation of psychometric properties of the maastricht upper extremity questionnaire (MUEQ) in Iranian computer users - Mohammad Ghasemi; Tahereh Kamalikhah; Mahmood Salesi; Fatemeh Rahmati (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Measurement of the essential risk factors for work-related musculoskeletal disorders is a fundamental step in predicting the problem and identifying high-risk individuals. In this regard, Maastricht upper extremity questionnaire (MUEQ) has not been validated in Iran. This study aimed to develop a valid and reliable Persian version of MUEQ. MATERIALS AND METHODS: In this descriptive study, the computer users employed in a governmental informatics administration in Tehran, Iran, were included during the end of 2018 and early 2019. Face and content validity of the MUEQ was conducted, and a six-part questionnaire was provided. The reliability of the questionnaire was obtained using Cronbach's α and test-retest. Concurrent validity was assessed with Nordic Musculoskeletal Questionnaire (NMQ). Exploratory and confirmatory factor analysis, comparison test of independent mean, internal consistency coefficient, test-retest, and Pearson correlation were carried out using the AMOS and SPSS 22 software. RESULTS: Participants consisted of 282 computer users (110 males) with a mean age of 35.17 ± 7.65 years. The mean duration of computer use in a working day was 6.68 ± 2.10 h with a range of 1-12 h. The most prevalent symptoms were existed in the neck (39.1%), back (31.0%), and lower back (30.3%) areas. KMO test and Bartlett's test of sphericity showed that a significant correlation existed among questions. Cronbach's alpha coefficient of the questionnaire varied from 0.61 to 0.83 and test-retest coefficient was higher than 0.7. Correlation coefficient was between NMQ and body posture (r = 0.23, P = 0.004) and between NMQ and work environment (r = 0.28, P = 0.000). Evaluations related to the construct validity and concurrent validity demonstrated that the questionnaire has acceptable construct validity. Six factors of the MUEQ in Root Mean Squared Error Approximation (RMSEA) index (0.062) were acceptable and satisfactory in Parsimony Comparative Fit Index (PCFI), Comparative Fit Index (CFI), Normed Fit Index (NFI), and Parsimony Goodness of Fit Index (PGFI) (0.732, 0.8000, 0.680, and 0.680, respectively). CONCLUSIONS: The Persian version of the MUEQ represented a satisfactory validity and reliability and was suitable for computer users in the assessment of their risk factors of musculoskeletal complaints.